Navigating mental health challenges in graduate school. - Murguía,Burton ZF; Cao,XE (Nat Rev Mater, 2022)
Many graduate students experience mental health struggles that lead them to question their place in academia. Two scientists who experienced extreme lows in graduate school reflect on what helped them during their low points, and suggest strategies for everyone to contribute to mentally healthier workplaces in academia.